The Correlation Between Students’ Vocabulary Mastery and Students’ Reading Comprehension in Narrative Text: English - Ukhtul Iffah; Albadri Albadri; Faizeh De Shofi Emilia (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2023)
This study was approached for finding out whether there was a significant correlation between students’ vocabulary mastery and students’ reading comprehension in narrative text or not. The researcher used quantitative research and correlation method, and there were two research variables, vocabulary mastery as variable X and reading comprehension as variable Y. The sample of this research was purposive sampling and 23 students taken. In collecting the data of this research, the researcher used multiple choice test consisted 20 item questions to measure students’ vocabulary mastery and their reading comprehension. The data was analyzed by using the formula of Product Moment (Pearson) through SPSS 16.0. The result of Product Moment (Pearson) was categorized strong with the coefficient correlation was 0.680 and the significance was 0.05, it meant that H0 was rejected and Ha was accepted. The result showed that there was a significant correlation between students’ vocabulary mastery and students’ reading comprehension in narrative text at the eighth grade of MTsS Lombok Kulon Wonosari Bondowoso in the academic year 2021/2022